2020
DOI: 10.1016/s1470-2045(19)30790-9
|View full text |Cite
|
Sign up to set email alerts
|

International standards for the analysis of quality-of-life and patient-reported outcome endpoints in cancer randomised controlled trials: recommendations of the SISAQOL Consortium

Abstract: This is a repository copy of International standards for the analysis of quality-of-life and patient-reported outcome endpoints in cancer randomised controlled trials: recommendations of the SISAQOL Consortium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
211
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 231 publications
(214 citation statements)
references
References 50 publications
2
211
0
1
Order By: Relevance
“…Two main reasons for this revision was indicated: the obvious changes in standard therapy and consequently emergence of new therapies that led to new different side effects, and the impacts of new drugs on patient’s quality of life [ 92 , 93 ]. Above all we think the new direction for setting international standards for the analysis of quality of life and patient-reported outcomes in cancer trials is a step forward to prevent disorganized reporting, and to encourage using appropriate instruments to measure quality of life in cancer patients in general and in breast cancer patients in particular [ 94 96 ].…”
Section: Discussionmentioning
confidence: 99%
“…Two main reasons for this revision was indicated: the obvious changes in standard therapy and consequently emergence of new therapies that led to new different side effects, and the impacts of new drugs on patient’s quality of life [ 92 , 93 ]. Above all we think the new direction for setting international standards for the analysis of quality of life and patient-reported outcomes in cancer trials is a step forward to prevent disorganized reporting, and to encourage using appropriate instruments to measure quality of life in cancer patients in general and in breast cancer patients in particular [ 94 96 ].…”
Section: Discussionmentioning
confidence: 99%
“…Measurement of HRQoL facilitates the calculation of quality-adjusted life years (QALY), defined as "the measure of the state of health of a person or group in which the benefits, in terms of length of life, are adjusted to reflect the quality of life" [17]. PROs are increasingly used as important endpoints in cancer clinical trials, and implementation has become more standardized [18,19]. Furthermore, studies have shown that using PROs in clinical practice leads to better patient-provider communication, more symptom control and patients are more willing to self-report their symptoms from home [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…In a report from the 5th EORTC Quality of Life in Clinical Cancer Trials Conference, 2019, it was stated that even in clinical trials there were no standards for PRO measurement, analysis and reporting, and a major issue may be to ensure that 'the right questions are asked and the right answers are communicated' [5]. To overcome these hurdles several scientific collaborations have attempted to provide guidelines for the use and analysis of PROs [6][7][8][9][10]. The International Society of Quality of life (ISOQOL) and the Standard Protocol Items: Recommendations for Interventional Trials (SPIRIT) PRO extension have provided key elements for the planning of PRO studies while the Setting International Standards in Analyzing Patient-Reported Outcomes and Quality of Life Endpoint Data (SISAQOL) Consortium has suggested international standards for analysis of QoL and PRO data in clinical trials which may assure that the impact of PRO in such studies is better aligned and not lost [9].…”
Section: Editorialmentioning
confidence: 99%
“…To overcome these hurdles several scientific collaborations have attempted to provide guidelines for the use and analysis of PROs [6][7][8][9][10]. The International Society of Quality of life (ISOQOL) and the Standard Protocol Items: Recommendations for Interventional Trials (SPIRIT) PRO extension have provided key elements for the planning of PRO studies while the Setting International Standards in Analyzing Patient-Reported Outcomes and Quality of Life Endpoint Data (SISAQOL) Consortium has suggested international standards for analysis of QoL and PRO data in clinical trials which may assure that the impact of PRO in such studies is better aligned and not lost [9]. We have previously demonstrated, how questionnaires developed to cover the same diagnosis and treatment situation may differ, leaving the risk of losing the potential of PROs [11] and have along with others suggested a systematic approach to following these guidelines in the question of item selection [12][13][14][15].…”
Section: Editorialmentioning
confidence: 99%